2016
DOI: 10.1186/s12263-016-0523-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profile adaptations following exposure of equine satellite cells to nutriactive phytochemical gamma-oryzanol

Abstract: BackgroundAdult skeletal muscle myogenesis depends on the activation of satellite cells that have the potential to differentiate into new fibers. Gamma-oryzanol (GO), a commercially available nutriactive phytochemical, has gained global interest on account of its muscle-building and regenerating effects. Here, we investigated GO for its potential influence on myogenesis, using equine satellite cell culture model, since the horse is a unique animal, bred and exercised for competitive sport. To our knowledge, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…GO is known to affect gene expression and several metabolic pathways related to inflammation [11,12] and oxidative stress [13]. Szczesniak et al [14] demonstrated that GO may affect different processes in differentiating equine satellite cells (ESCs), including inhibition of myoblast differentiation, and increased proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…GO is known to affect gene expression and several metabolic pathways related to inflammation [11,12] and oxidative stress [13]. Szczesniak et al [14] demonstrated that GO may affect different processes in differentiating equine satellite cells (ESCs), including inhibition of myoblast differentiation, and increased proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The mRNA sequences of genes were obtained from the NCBI Nucleotide database. Primer sequences were designed using the Primer3 ( ) and Primer-Blast software ( ) and then checked using Oligo Calculator ( ) as described previously [ 84 ]. Primer sequences, annealing temperatures, and product length measurements are listed in Table S4 .…”
Section: Methodsmentioning
confidence: 99%
“…The mRNA sequences of the genes selected for validation were obtained from the NCBI Nucleotide database. Primer sequences were designed using the Primer3 and Primer-Blast software (NCBI database) and then checked using Oligo Calculator as described previously (Szcześniak et al 2016 ). The sequences of the designed primers are listed in Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%